Visible vs Silent Protest: Explaining Divergent Outcomes on Single-Candidate Local Elections in Indonesia - Hafidz, Moh. Maskurudin; Nailufar, Faza Dhora; Sembiring, Odri Prince Agustinus D; Rohi, Rudi (Faculty of Social and Political Science Universitas Brawijaya, 2025)
This study investigates the puzzling phenomenon of divergent outcomes in single-candidate local elections (Pilkada) across Indonesia. Employing a mixed-methods sequential explanatory design, this study undertakes a comparative analysis of three cases from the 2024 Pilkada in Bangka, Bangka Selatan, and Pangkalpinang, which are located within Bangka Belitung Islands Province. The approach utilizes quantitative survey data from 455 voters and qualitative document analysis. The results suggest that the key determinant of the blank vote's success or failure is the voter's evaluation of the incumbent's performance. Inadequate evaluations of the incumbent's performance in Bangka and Pangkalpinang served as a catalyst, converting a pre-existing crisis of representation into a successful protest vote. Conversely, high public satisfaction with governance in Bangka Selatan served as a protective barrier, neutralizing the impulse for protest despite the non-competitive electoral format. The analysis delineates two separate mobilization tactics for achieving victory: a